Determination of the strong coupling constant αs(mZ) from measurements of the total cross section for top–antitop-quark production - Klijnsma, T; Bethke, S; Dissertori, G; Salam, G (Springer, 2017)
We present a determination of the strong coupling constant αs(mZ) using inclusive top-quark pair production cross section measurements performed at the LHC and at the Tevatron. Following a procedure first applied by the CMS Collaboration, we extract individual values of αs(mZ) from measurements by different experiments at several centre-of-mass energies, using QCD predictions complete in NNLO perturbation theory, supplemented with NNLL approximations to all orders, and suitable sets of parton distribution functions. The determinations are then combined using a likelihood-based approach, where special emphasis is put on a consistent treatment of theoretical uncertainties and of correlations between various sources of systematic uncertainties. Our final combined result is αs(mZ)=0.1177+0.0034−0.0036